Alcohol consumption among university students: a Sino-German comparison demonstrates a much lower consumption of alcohol in Chinese students. Issue 1 (December 2016) - Chu, Janet; Jahn, Heiko; Khan, Mobarak; Kraemer, Alexander
Abstract Background Alcohol use is reported in university students with discrepancy between countries. The study objectives were to assess prevalence and associated factors of alcohol consumption among university students in Germany and China. Methods Data used were from 1853 Chinese and 3306 German university students. Alcohol consumption frequency was measured by a question "How often did you drink alcohol in the last three months?" with six possible responses, which were later collapsed into three categories of "At least once a week", "Less than once a week" and "Never". Problem drinking was measured by the CAGE test and defined as a CAGE score of two or more (four as the maximum). Simple and multivariable logistic regressions were used for association analyses. Results German students reported more often "At least once a week" drinking (59.8 vs. 9.0 %). Among Germans, women drank less often "At least once a week" (OR = 0.40, 0.30–0.53). Among Chinese, a higher BMI was associated with drinking "At least once a week" (OR = 1.09, 1.02–1.18). Age revealed a positive association with "At least once a week" drinking in Chinese (1.33, 1.21–1.46) but a negative association in Germans (OR = 0.97, 0.94–0.99). Having a father with high educational level was positively related to "At least once a week" drinking in both countries (OR = 4.25, 2.67–6.78 for Chinese; OR = 1.32, 1.01–1.72 for Germans). Doing less than once a week physical exercise was negatively associated with "At least once a week" drinking in Chinese and German students (OR = 0.27, 0.15–0.48 for Chinese; OR = 0.69, 0.49–0.96 for Germans). Among the German students, 20.3 % reported problem drinking. Being a female (OR = 0.32, 0.26–0.40) and performing less than once a week physical activity (OR = 0.73, 0.56–0.95) were negatively associated with problem drinking, while having a father with high educational level (OR = 1.32, 1.09–1.60) and experiencing higher level of perceived stress (OR = 1.08, 1.04–1.13) were positively related to problem drinking. Conclusions Country-specific strategies for reducing alcohol consumption, e.g. educational awareness programmes of alcohol use on Chinese campuses and alcohol prevention schemes among German youth before entering university, are sensible.